2009
DOI: 10.1200/jco.2008.18.3939
|View full text |Cite
|
Sign up to set email alerts
|

Oral Uracil and Tegafur Compared With Classic Cyclophosphamide, Methotrexate, Fluorouracil As Postoperative Chemotherapy in Patients With Node-Negative, High-Risk Breast Cancer: National Surgical Adjuvant Study for Breast Cancer 01 Trial

Abstract: RFS and OS with oral UFT were similar to those with classical CMF. Given the higher QOL scores, oral UFT is a promising alternative to CMF for postoperative adjuvant chemotherapy in women with node-negative, high-risk breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 27 publications
2
54
1
Order By: Relevance
“…Similar findings were recently reported in a randomised study of stage I -IIIA node-negative, pathologically high-risk breast cancer, which compared a 2-year administration of UFT with 6 cycles of CMF (Watanabe et al, 2009). Results indicated that the efficacy of UFT as an adjuvant treatment was comparable with that of CMF.…”
Section: Resultssupporting
confidence: 86%
“…Similar findings were recently reported in a randomised study of stage I -IIIA node-negative, pathologically high-risk breast cancer, which compared a 2-year administration of UFT with 6 cycles of CMF (Watanabe et al, 2009). Results indicated that the efficacy of UFT as an adjuvant treatment was comparable with that of CMF.…”
Section: Resultssupporting
confidence: 86%
“…Only 7 of these trials provided reference to historical data. A trial in breast cancer determined the noninferiority margin by a clinically leastacceptable HR of tegafur-uracil as compared with cyclophosphamide 镁 methotrexate 镁 5-fluorouracil (5-FU; CMF), derived from a structured questionnaire among investigators (21). Among the 6 trials using the effect retention method, a retention proportion of 50% was most frequent (5 trials).…”
Section: Methods For Selecting a Noninferiority Marginmentioning
confidence: 99%
“…In 2009, the results of the National Surgical Adjuvant Study for Breast Cancer 01 Trial (NSAS-BC01) [7] and the Comparative Trial of UFT + Tamoxifen with CMF + Tamoxifen in Adjuvant Therapy for Breast Cancer (CUBC) [8] -two recent Japanese clinical trials designed to establish whether intravenous or oral treatment was superior for postoperative adjuvant chemotherapy -were reported. The NSAS-BC01 trial compared CMF with UFT in high-risk patients with axillary node negative breast cancer.…”
Section: Chemotherapymentioning
confidence: 99%